Breeding potential of maize composite Isanao VF1 in small spacing in the second growing season - Candido, Liliam Silvia [UNESP]; da Costa Andrade, Joao Antonio [UNESP] (Brazilian Soc Plant Breeding, 2008)
The purpose of this study was to verify the breeding potential of the maize composite Isanao VF1 in the second growing season. One hundred and fifty half-sib progenies were evaluated of spacing of 0.45 m, densities of 57,778 and 80,000 plants ha(-1), in a randomized block design with three replications. Gains of 16.0 and 19.2% were estimated for grain Yield, H. I and 10.5% for prolificacy and 12.3 and 12.9% for ear height, respectively, at 57,778 and 80,000 plants ha(-1). The heritabilities for plant height, ear height and grain yield were 65.2 and 61.3%, 64.3 and 66.9% and 53.5 and 63.3%, respectively, confirming the potential for breeding at both densities. The absence of progeny by density interaction indicates that no further selection programs are necessary. The occurrence of segregation for modifier genes for height suggests stabilizing selection based on ear height.
Keywords: plant arrangement; Sowing density; genetic variation; Genetic parameter